Natural ventilation for energy efficient office buildings: a comparative analysis on three buildings in Kuala Lumpur - Naamandadin, Nurul Akmam; Zainol, Noorazman Zaiha; Mohd Noor, Siti Nur Aishah; Sapian, Abdul Razak (Universiti Tun Hussein Onn Malaysia, 2019)
Natural ventilation is one of the criteria of passive design strategies to reduce the usage of active ventilation especially an air-conditioning system which will involve a hugeamount of operation cost. The aim of this study was to identify and analyse the criteria of natural ventilation in the selected office buildings. The analysis had been made based on the architectural and passive design component provided in MS 1525:2007 for the office building. This case study is important in helping to understand the relationship between natural ventilation, energy efficiency and cost effectiveness